Temporal and spatial heterogeneity of the Ailaoshan–Song Ma–Song Chay ophiolitic mélange, and its significance on the evolution of Paleo-Tethys - Lin, Wei; Liu, Fei; Wang, Yin; Meng, Lingtong; Faure, Michel; Chu, Yang; Nguyen, Vuong Van; Wu, Qinying; Wei, Wei; Thu, Hoai Luong Thi; Vu, Tich Van (Comptes Rendus. Géoscience)
According to detrital zircons ages spectra and Hf isotopes in the matrix of the ophiolitic mélange, the Ailaoshan–Song Ma–Song Chay Indosinian suture zone can be divided into four units, namely M1, M2, M3, and M4. Different deposition ages (310–270 Ma, 260–255 Ma, ${\sim }$245 Ma, and ${>}$255 Ma) demonstrate temporal heterogeneity. The M1 unit is in the middle and south segments, and inner part of the NW segment of the Ailaoshan ophiolitic mélange, and the southernmost part of Song Ma ophiolitic mélange. The Silurian and Devonian sedimentary rocks of the Indochina block are the major provenance of the M1 unit. The M2 unit is located in the southwest part of the NW segment of the Ailaoshan ophiolitic mélange. At least half of the 270–250 Ma detrital zircons might come from the South China block. The M3 unit is mainly located in the Ailaoshan–Song Ma ophiolitic mélange and sourced from Indochina block. M4 is mainly located in the Song Chay ophiolitic mélange, and its detrital zircons are mainly sourced from the South China block. The strike-parallel heterogeneity refers to the different distributions along the orogenic belt with various provenances. The strike-perpendicular heterogeneity characterises the geometry of M1, M2, and M3 units and is attributed to a Cenozoic positive-flower structure of the Red River Fault showing sinistral strike-slip tectonic event with SW-ward thrusting. These temporal and spatial heterogeneities correspond well to the different evolutionary stages of the eastern Paleo-Tethys.